Analysis of User Satisfaction Towards Online Food Ordering Services and Prices Using Customer Satisfaction Index - Liu, Jonathan; Hendrik, Jackri; Tarigan, Feriani Astuti (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The rapid growth of application-based food delivery services in Indonesia highlights the importance of not only convenience and delivery speed but also user satisfaction. This study aims to develop a digital survey system and management application capable of automatically calculating the Customer Satisfaction Index (CSI), analyzing key user satisfaction indicators, and comparing satisfaction levels across multiple platforms. The CSI method was employed to evaluate user satisfaction based on indicators such as service quality, application usability, delivery speed, pricing, and promotional offers. Data were collected through questionnaires completed by 200 active users of GoFood, GrabFood, and ShopeeFood, with each indicator measured using a five-point Likert scale to assess both importance and satisfaction. The findings reveal that delivery time significantly influences user satisfaction, with GoFood achieving the highest CSI score in the delivery aspect at 60.58%. In contrast, ShopeeFood outperformed in the pricing dimension, with transparency and price accuracy rated as the most satisfactory. However, undisclosed additional charges were identified as a factor that reduced overall satisfaction. This study is expected to provide valuable insights for food delivery application providers to enhance service quality and foster customer loyalty.